Hubungan Kecerdasan Emosi dan Pola Asuh Demokratis Orang tua dengan Prokrastinasi Akademik pada Mahasiswa Fakultas Psikologi Universitas Medan Area - Palentinus Tarigan; Risydah Fadilah; Abdul Murad (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The purpose of this study was to examine the correlation between emotional intelligence and parenting democratic with academic procrastination of College Students Faculty Of Psychology batch 2015 and 206, Medan Area University. The approach used in this study was a quantitative approach. The samples technique in this study was an accidental sampling. In this study, the researcher used three scale measuring as the instrument type. The scale used to measure the academic procrastination, emotional intelligence and parenting democratic scale. The data analysis techniques used in this study was a multiple regression analysis. Based on the analysis of data the results show that: (1). There was a negative significant relationship between parenting democratic with academic procrastination which was seen from R= -0,863 and R2=0,745 where p < 0.05. (2). There was a negative significant relationship between parenting democratic with academic procrastination which was seen from R= -0,461 and R2=0,213 where p < 0.05. (3). There was a significant relationship between emotional intelligence and parenting democratic with academic procrastination which was seen from coefficient value of R2=0,759. It means that there was a significant correlation emotional intelligence and social support with academic procrastination college students Faculty of Psychology batch 2015 and 2016, Medan Area University.